'Pride and Joy': Propaganda Wars, 'Projections of America' and the Dismantling of the Office of War Information at the Close of World War II. Issue 4 (2nd October 2019) - Scott, Ian
Abstract : The OWI was the key agency for the distribution and dissemination of US film and propaganda during World War II. But it was the Overseas Branch of the OWI that dominated activity and the Motion Picture Unit (MPU) of the OB that helped shape documentary production through the portrayal of American values and society. The OWI's winding up at war's end has long been seen as part of a natural reversion to peacetime government policy. Yet, as this article argues, events within the MPU/OWI in the last year of the war throw up evidence that suggests the agency was being deliberately sidelined – even undermined – in preparation for a more rigorous and ideological post-war propaganda apparatus. This revised propaganda philosophy was set in train by a select number of individuals, principally historian Edward Lilly, newspaperman C.D. Jackson, and the army's Brig Gen Robert McClure. Their scrutiny of the MPU/OWI – accessed via private correspondence and archival papers – is revealed for the first time in this article and is explained away as a self-conscious move away from civilian and towards military propaganda authority and control in the emergent Cold War era.